2020
DOI: 10.1007/s13311-020-00895-6
|View full text |Cite
|
Sign up to set email alerts
|

Reperfusion plus Selective Intra-arterial Cooling (SI-AC) Improve Recovery in a Nonhuman Primate Model of Stroke

Abstract: Early reperfusion is increasingly prioritized in ischemic stroke care, but outcomes remain suboptimal. Therefore, there is an urgent need to find neuroprotective approaches that can be combined with reperfusion to maximize efficacy. Here, the neuroprotective mechanisms behind therapeutic hypothermia were evaluated in a monkey model of ischemic stroke. Focal ischemia was induced in adult rhesus monkeys by placing autologous clots in the middle cerebral artery. Monkeys were treated with tissue plasminogen activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…We believe that some of the beneficial effects of this method could be due to mechanical flushing, increasing vessel patency and promoting vasorelaxation and hemodilution. This protocol also showed advantages in monkey stroke models and patients with stroke ( 80 ). Interestingly, several animal studies have reported that the combination of cold saline and magnesium sulfate (acting as an N -methyl- d -aspartate receptor antagonist that prevents excitotoxic cell damage) or low-dose albumin (improving microcirculation with multiple neuroprotective properties) has greater neuroprotective advantages than cold saline alone ( 81 ).…”
Section: Methodological Descriptions Of Selective Brain Coolingmentioning
confidence: 99%
“…We believe that some of the beneficial effects of this method could be due to mechanical flushing, increasing vessel patency and promoting vasorelaxation and hemodilution. This protocol also showed advantages in monkey stroke models and patients with stroke ( 80 ). Interestingly, several animal studies have reported that the combination of cold saline and magnesium sulfate (acting as an N -methyl- d -aspartate receptor antagonist that prevents excitotoxic cell damage) or low-dose albumin (improving microcirculation with multiple neuroprotective properties) has greater neuroprotective advantages than cold saline alone ( 81 ).…”
Section: Methodological Descriptions Of Selective Brain Coolingmentioning
confidence: 99%
“…Intermittent positive pressure ventilation was performed for monkeys with a fixed respiratory rate. Non-invasive blood pressure, electrocardiogram, heart rate, oxygen saturation, blood gas, and rectal temperature were monitored ( Wu et al, 2020a , b , c ).…”
Section: Methodsmentioning
confidence: 99%
“…Collecting baseline and series of anatomical imaging permits the longitudinal assessments of brain atrophy and white matter tractography integrity. 20 Salvaged tissue or diffusion lesion reversal has been explored in monkey models after stroke onset. 21 Another advantage is to biopsy brain tissue based on imaging identification of the target, which can facilitate molecular analyses.…”
Section: Imaging Evaluation and Long-term Functional Outcomesmentioning
confidence: 99%